Native American Voices: Decolonial Perspectives on Selected Texts of Alexie and Momaday - Dr. Sadia Akram; Dr. Sadia Nazir; Saira Akhter (NUML Journal of Critical Inquiry)
This paper explores the Native American voices through a decolonial reading of a range of selected texts of Sherman Alexie and Navarre S. Momaday. The aim is to understand indigenous culture as a prototype for retrieving the lost identity of American Indians. The decolonization of mind is realized through cultural resistance and counter-discourse that articulates the liminal experiences of the marginalized and the ostracized. Therefore, the literary representation of peripheral voices not only defies the dominant voice but also creates new avenues for cross-cultural communication with the mainstream discourse. This study employs the dialogic approach of Greg Sarris and Louis Owens as theoretical support for analysing the selected texts. The slippery frontier position of American Indians is not separatist but conversational that subverts stereotypes and, simultaneously, acknowledges difference. This essay principally explores how cross-reading Native American subversive texts can serve as a tool for cross-cultural communication. The indigenous writers with their lost identity (due to their living on reservations) write passionately about their past, traditions, and customs to make their voice heard in the mainstream discourse for their survival. This paper, therefore, proposes that the gap between Natives and Euro-Americans may be bridged through literary resistance for reconciliation instead of creating antagonism between them.